Search for Minimal Supersymmetric Standard Model Higgs bosons H/A and for a Z boson in the ττ final state produced in pp collisions at √s = 13 TeV with the ATLAS Detector - Dova, María Teresa (2016)
Asearch for neutral Higgs bosons of the minimal supersymmetric standard model (MSSM) and for a heavneutral Z boson is performed using a data sample corresponding to an integrated luminosity of 3.2 fb−1 from proton–proton collisions at √s = 13 TeV recorded by the ATLAS detector at the LHC. The heavy resonance is assumed to decay to a τ+τ− pair with at least one τ lepton decaying to final states with hadrons and a neutrino. The search is performed in the mass range of 0.2–1.2 TeV for the MSSM neutral Higgs bosons and 0.5–2.5 TeV for the heavy neutral Z boson. The data are in good agreement with the background predicted by the Standard Model. The results are interpreted inMSSMand Z benchmark scenarios. The most stringent constraints on theMSSM mA–tan β space exclude at 95%confidence level (CL) tanβ > 7.6 for mA = 200 GeV in the mmod+ h MSSM scenario. For the Sequential Standard Model, a Z SSM mass up to 1.90 TeV is excluded at 95% CL and masses up to 1.82–2.17 TeV are excluded for a Z SFM of the strong flavour model.